DESCRIPTION OF THE FIRST RECORD OF THE INDIAN FALSE VAMPIRE BAT (Megaderma lyra) E. Geoffroy, 1810 (RHINOPOMATIDAE: CHIROPTERA) CAPTURED FROM NORTHWESTERN PAKISTAN - M. Salim; M. Mahmood-ul-Hassan (Journal of Animal and Plant Sciences, 2014)
The greater false vampire bat Megaderma lyra is an Indomalayan bat species. Although this species has been reported from Punjab, Sind and Baluchistan, no specimen has been captured from Khyber-Pakhtunkhwa (KP).We report its occurrence further northwest of Pakistan in Malakand district where 40 greater false vampire bats were recorded roosting in a chromite mine at Heroshah of tehsil Dargai. We used a hand net to capture the bats. Upon examination it was found that all were females. The captured bats were identified on the basis of their unique facial appearance, an erect and elongated nose-leaf and large oval ears that joined on the forehead. This paper documents craniomorphometeric characteristics of the greater false vampire bats inhabiting northwestern part of the country and compares with previous available records.
Keywords: First record; Malakand; Heroshah; Chiroptera